A proportion of CD4+ T cells from patients with chronic Chagas disease undergo a dysfunctional process, which is partially reversed by benznidazole treatment. - Elena Pérez-Antón; Adriana Egui; M Carmen Thomas; Bartolomé Carrilero; Marina Simón; Miguel Ángel López-Ruz; Manuel Segovia; Manuel Carlos López (Public Library of Science (PLoS), 2021)
Background Signs of senescence and the late stages of differentiation associated with the more severe forms of Chagas disease have been described in the Trypanosoma cruzi antigen-specific CD4+ T-cell population. However, the mechanisms involved in these functions are not fully known. To date, little is known about the possible impact of benznidazole treatment on the T. cruzi-specific functional response of CD4+ T cells. Methodology/principal findings The functional capacity of CD4+ T cells was analyzed by cytometric assays in chronic Chagas disease patients, with indeterminate form (IND) and cardiac alterations (CCC) (25 and 15, respectively) before and after benznidazole treatment. An increase in the multifunctional capacity (expression of IFN-γ, IL-2, TNF-α, perforin and/or granzyme B) of the antigen-specific CD4+ T cells was observed in indeterminate versus cardiac patients, which was associated with the reduced coexpression of inhibitory receptors (2B4, CD160, CTLA-4, PD-1 and/or TIM-3). The functional profile of these cells shows statistically significant differences between IND and CCC (p<0.001), with a higher proportion of CD4+ T cells coexpressing 2 and 3 molecules in IND (54.4% versus 23.1% and 4.1% versus 2.4%, respectively). A significant decrease in the frequencies of CD4+ T cells that coexpress 2, 3 and 4 inhibitory receptors was observed in IND after 24-48 months of treatment (p<0.05, p<0.01 and p<0.05, respectively), which was associated with an increase in antigen-specific multifunctional activity. The IND group showed, at 9-12 months after treatment, an increase in the CD4+ T cell subset coproducing three molecules, which were mainly granzyme B+, perforin+ and IFN-γ+ (1.4% versus 4.5%). Conclusions/significance A CD4+ T cell dysfunctional process was detected in chronic Chagas disease patients, being more exacerbated in those patients with cardiac symptoms. After short-term benznidazole treatment (9-12 months), indeterminate patients showed a significant increase in the frequency of multifunctional antigen-specific CD4+ T cells.